A Widely Distributed Biosynthetic Cassette Is Responsible for Diverse Plant Side Chain Cross‐Linked Cyclopeptides. Issue 7 (12th January 2023) - Lima, Stella T.; Ampolini, Brigitte G.; Underwood, Ethan B.; Graf, Tyler N.; Earp, Cody E.; Khedi, Imani C.; Pasquale, Michael A.; Chekan, Jonathan R.
Abstract: Cyclopeptide alkaloids are an abundant class of plant cyclopeptides with over 200 analogs described and bioactivities ranging from analgesic to antiviral. While these natural products have been known for decades, their biosynthetic basis remains unclear. Using a transcriptome‐mining approach, we link the cyclopeptide alkaloids from Ceanothus americanus to dedicated RiPP precursor peptides and identify new, widely distributed split BURP peptide cyclase containing gene clusters. Guided by our bioinformatic analysis, we identify and isolate new cyclopeptides from Coffea arabica, which we named arabipeptins. Reconstitution of the enzyme activity for the BURP found in the biosynthesis of arabipeptin A validates the activity of the newly discovered split BURP peptide cyclases. These results expand our understanding of the biosynthetic pathways responsible for diverse cyclic plant peptides and suggest that these side chain cross‐link modifications are widely distributed in eudicots. Abstract : Cyclopeptide alkaloids are a diverse class of plants natural products, yet little is known of their biosynthesis. By combining transcriptomics and genome mining, we uncover a widespread biosynthetic cassette responsible for side chain cross‐linked cyclopeptides. We validate these observations by isolating a new cyclopeptide from Coffea arabica and reconstituting enzymatic activity for the family defining split BURP peptide cyclase.